Dynamic recrystallization behavior and transformation mechanism in β-phase region of TB17 titanium alloy - ZHU Hong-chang; LUO Jun-ming; ZHU Zhi-shou (Cailiao gongcheng, 2019)
The thermal compression experiment of TB17 titanium alloy in the β phase region was carried out by Gleeble-3800 hot compression simulator. The dynamic recrystallization behavior and transformation mechanism in the β phase region of the TB17 titanium alloy were studied. The results show that the dynamic recovery (DRV) and dynamic recrystallization (DRX) occur in the β-phase region during deformation process of the TB17 titanium alloy. There are two dynamic recrystallization nucleation sites at different strain rates. At low strain rate, it mainly nucleates inside the grains, and at high strain rate, it is near the grain boundary. According to EBSD and TEM analyses, the main mechanism happened at low strain rate is continuous dynamic recrystallization (CDRX) which mainly is controlled by sub-grain rotation. Discontinuous dynamic recrystallization (DDRX) occurs at high strain rates, the main form of deformation is grain boundary shear accompanied by sub-grain rotation. Although the two dynamic recrystallizations are transformed in different ways, the essence is to form new dynamic recrystallized grains through the propagation, slip and cell structure evolution of dislocations.